Antibiotic residue analysis of tetracycline and chloramphenicol in banana shrimp (Fenneropenaeus merguiensis) from a traditional shrimp farming in Brondong, Lamongan - Sapto Andriyono; Alma Ika Fatmawati; Nuning Vita Hidayati; Mirna Fitrani; Boedi Setya Rahardja (Grouper: Jurnal Ilmiah Fakultas Perikanan Universitas Islam Lamongan, 2023)
Banana shrimp is one of the potential export shrimp cultivated in Brondong, Lamongan. Antibiotic residues, including pollutants, can come from cultivation pond areas and environmental pollution. The antibiotics in shrimp are tetracycline groups (oxytetracycline, chlortetracycline, and tetracycline) and chloramphenicol.Â  This study aims to determine the presence of antibiotic residues in banana shrimp and whether the quality of the shrimp has met health safety standards based on antibiotic residue analysis using estimated daily intake (EDI) and hazard quotient (HQ) calculations. Examination of antibiotic residues is carried out at the UPT. Quality Testing and Development of Marine and Fisheries Products in Surabaya. This study used an observation method by taking shrimp samples, measuring pond water quality parameters, and testing the content of antibiotic residues in the laboratory. The examination results showed that residues of the tetracycline and chloramphenicol groups were not detected in banana shrimp. Calculations of EDI and HQ cannot be performed because antibiotic residues are not detected. The HQ value is below one, which indicates a low-risk level category. Banana shrimp from a farming pond in Brondong, Lamongan is safe for human consumption.